Environmental Humanities South: Decolonizing Nature in Highland Asia - Dan Smyer Yü; Ambika Aiyadurai; Mamang Dai; Razzeko Delley; Rashila Deshar; Iftekhar Iqbal; Chi Huyen Truong; Bhargabi Das; Mongfing Lepcha; Thinley Dema; Madan Koirala; Zainab Khalid; et al. (Challenges, 2025)
We, a group of native scholars based in the Himalayan region, co-author this article to propose an environmental humanities South—concurrently as an Asia-specific interdisciplinary field and a planetary human–nature epistemology of the Global South inextricably entwined with that of the Global North. Framed in the broader field of planetary health, this article begins with a perspectival shift by reconceptualizing the Global South and the Global North as the Planetary South and the Planetary North for the purpose of laying the epistemological groundwork for two interconnected arguments and subsequent discussions. First, the Planetary South is not merely epistemological, but is at once geographically epistemological and epistemologically geographical. Our debates with the currently dominant epistemologies of the South open up a decolonial conversation with what we call the Australian School of the environmental humanities, the initial seed bank of our interdisciplinary environmental work in Asia’s Planetary South. These multilayered epistemological debates and conversations lead to the second argument that the South and the North relate to one another simultaneously in symbiotic and paradoxical terms. Through these two arguments, the article addresses the conundrum of what we call the “postcolonial continuation of the colonial environmentality” and attempts to interweave the meaningful return of the eroding Himalayan native knowledges of nature with modern scientific findings in a way that appreciates the livingness of the earth and is inclusive of nonwestern environmental worldviews.